Disparities and guideline adherence in drugs of abuse screening in intracerebral hemorrhage. (17th January 2017) - Tormoehlen, Laura M.; Blatsioris, Ashley D.; Moser, Elizabeth A.S.; Carter, Ravan J.L.; Stevenson, Alec; Ofner, Susan; Hulin, Abigail L.; O'Neill, Darren P.; Cohen-Gadol, Aaron A.; Leipzig, Thomas J.; Williams, Linda S.; Mackey, Jason
Abstract : Objective: To characterize the pattern of urine drug screening in a cohort of intracerebral hemorrhage (ICH) patients at our academic centers. Methods: We identified cases of primary ICH occurring from 2009 to 2011 in our academic centers. Demographic data, imaging characteristics, processes of care, and short-term outcomes were ascertained. We performed logistic regression to identify predictors for screening and evaluated preguideline and postguideline reiteration screening patterns. Results: We identified 610 patients with primary ICH in 2009–2011; 379 (62.1%) were initially evaluated at an outside hospital. Overall, 142/610 (23.3%) patients were screened, with 21 positive for cocaine and 3 for amphetamine. Of patients <55 years of age, only 65/140 (46.4%) were screened. Black patients <55 years of age were screened more than nonblack patients <55 years of age (38/61 [62.3%] vs 27/79 [34.2%]; p = 0.0009). In the best multivariable model, age group ( p = 0.0001), black race ( p = 0.4529), first Glasgow Coma Scale score ( p = 0.0492), current smoking ( p < 0.0001), and age group × black race ( p = 0.0097) were associated with screening. Guideline reiteration in 2010 did not improve the proportion <55 years of age who were screened: 42/74 (56.8%) were screened before and 23/66 (34.9%) after ( p = 0.01). Conclusions: We found disparities in drugs of abuse (DOA) screening and suboptimal guideline adherence. Systematic efforts to improve screening for DOA are warranted. Improved identification of sympathomimetic exposure may improve etiologic classification and influence decision-making and prognosis counseling.